The effectiveness of promotional mix in creating public awareness towards the products of Celcom during event/road show in Melaka / Mohd Razman Ramli - Ramli, Mohd Razman (Faculty of Business and Management, 2008)
One Two Three Communication (M) Sdn. Bhd. is the only one Celcom's dealer in Melaka that have an authority to organize various functions and events of Celcom around Melaka. One Two Three Communication (M) Sdn. Bhd. always ensures that they have sufficient advertisement and publicity to enhance customers' awareness. But this company needs more to ensure either the promotion mix used by them is effective or not in order to enhance public awareness towards products offered in Celcom event. In this study, One Two Three Communication (M) Sdn. Bhd. seems to face several problems especially in ensuring either the promotion mix used by company will enhance level of public awareness or the other way round. Based on result, it shows that most of respondents chose sales promotion as an effective promotion mix for One Two Three Communication to promote Celcom's product during the event or road shows that they Organized. Most of respondents chose sales promotion because these promotion tools will savings their money and gift benefits to them. Based on result also most of respondents are very aware with Celcom's product during event or road show through promotion mix used by One Two Three Communication.